Interpreting the Tinnitus Questionnaire (German version): what individual differences are clinically important? - Hall, Deborah A.; Mehta, Rajnikant; Argstatter, Heike (Taylor & Francis, 2018)
Objective: Reporting of clinical significance is recommended because findings can be statistically significant without being relevant to patients. For aiding clinical interpretation of the Tinnitus Questionnaire (TQ), many investigators use a 5-point change cut-off as a minimal clinically important difference (MCID). But there are shortcomings in how this value was originally determined. Design: The MCID was evaluated by analysing retrospective clinical data on the TQ (German version). Following recommended standards, multiple estimates were computed using anchor- and distribution-based statistical methods. These took into account not only patients’ experience of clinical improvement, but also measurement reliability. Study sample: Pre- and post-intervention scores were assessed for 202 patients. Results: Our six estimates ranged from 5 to 21 points in TQ change score from pre- to post- intervention. The 5-point TQ change score was obtained using a method that considered change between groups, and did not account for measurement error or bias. The size of the measurement error was considerable, and this comprises interpretation of individual patient change scores. Conclusions: To enhance confidence that a TQ change over time in individual patients is clinically meaningful, we advise at least the median MCID of 12 points.